Lessons learned from cross-sectoral collaboration to protect migrant farmworkers during COVID-19 in Spain - Miquel Úbeda; Vanesa Villa-Cordero; Agustín González-Rodríguez; Sergio Andrés-Cabello; Iratxe Perez-Urdiales; María del Mar Jiménez-Lasserrotte; Mar Pastor-Bravo; Erica Briones-Vozmediano (PLoS ONE, 2025)
In Spain, the agricultural sector relies heavily on migrant workers, especially during seasonal seasons. However, these workers face significant challenges related to precarious working conditions and structural vulnerability, which have become more acute since the outbreak of the COVID-19 pandemic. This descriptive qualitative study was based on 87 personal interviews with health and social professionals from sectors such as NGOs, social services, trade unions, local institutions, and health services to promote compliance with these measures in four Spanish regions. It explored the difficulties faced by migrant agricultural workers in complying with prevention measures during the COVID-19 pandemic, the measures taken by organizations and public institutions and the health consequences of the pandemic on this group. After a reflexive thematic analysis, the results show how to mitigate the pandemic’s impact, both local authorities and NGOs implemented extraordinary measures to care for migrant farm workers. Responses to the pandemic included temporary housing, mass testing, and stricter labor regulations. Working conditions, constant mobility, precarious housing, and language barriers contributed to the difficulty of implementing preventive measures. Covid-19 intensified inequalities and highlighted the lack of preparedness of institutions to deal with this group. The conclusions suggest that intercultural competence in health professional training and the creation of inclusive approaches to health and social care are critical to addressing health disparities and ensuring the well-being of all migrant farm workers, regardless of their migration status or mobility.